PHYSICS OF QUR'AN: ISLAMIZING THE SCIENCE AND ITS CONTRIBUTION TOWARDS HUMANITY - Dawam Multazamy Rohmatulloh; Arik Dwijayanto (Universitas Pendidikan Indonesia, 2021)
Physics is a fundamental science in the development of science and technology in the modern world. Physics studies the various forms of structure and character of natural objects. Thus, mastery of physics is one of the activities desired by Allah Swt. This article is made so that at least the Muslim community can realize the urgency of physics. In this study, we use the type/approach of research in the form of Library Research. The data that we obtain and process is data that comes from manuscripts or texts from similar previous studies. From this research, we conclude that the Qur'an is a way of life for all mankind. The Qur'an is like a miniature of the universe that contains all disciplines of science and is a means of solving all problems throughout human life. Besides that, physics has a very large and significant function and role in the existence of mankind. Also, the role of this physical science can ease the difficulties experienced by lightening the work of humans is not difficult.